Association between dietary sodium, calcium, saturated fat and blood pressure in obese Egyptian adolescents - Nayera E. Hassana; Salwa M. El Shebinib; Sahar A. El-Masrya; Nihad H. Ahmedb; Manal M. Alia; Gamila S. M. El-Saeedc; Dalia El-Lebedyd (SpringerOpen, 2019)
Abstract Background Overweight/obesity, high dietary fat, sodium and low calcium intake are recognized as risk factors for primary hypertension in obese adults, children and adolescents. Aim The aim of this work was to assess the association between some dietary factors (fat, sodium, calcium) and blood pressure (BP) among obese Egyptian adolescents. Subjects and methods Seventy-seven adolescents shared in this study. Their height and weight were reported. Body mass index (BMI) was calculated. Blood pressure was measured; the mean values were corrected for age and sex in the form of centile. Dietary interview consisting of 24 h recall was performed. Fasting blood glucose and serum lipid profile were determined. Results Data revealed that, the percent of the prehypertensive was 42.86% and 38.80%, for boys and girls, no hypertensive cases were recorded. The mean values of their weight, DBP, and the serum lipid parameters were high compared to their controls; significant differences were found between the daily intake of calories, protein, carbohydrate, dietary fiber and cholesterol at p ≤ 0.05. The mean values of the daily intake of the vitamins and minerals were low in all groups compared to the RDAs, except sodium intake which was high in the prehypertensive boys and normal and prehypertensive girls. Conclusion This study showed a high incidence of pre-hypertension among obese Egyptian adolescents, which is associated with high intake of sodium, saturated fat and cholesterol, along with low intake of calcium.